2010
DOI: 10.1016/s1348-8643(10)80009-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biological Apatite Orientation in Rat Mandibles

Abstract: Recently, significant progress has been made in medical techniques for regenerating bone. However, bone evaluation techniques generally assess bone quantity as opposed to bone quality. The use of c‐axis crystallite orientation of biological apatite (BAp) as a bone quality index has recently generated great interest. BAp demonstrates strong crystallographic anisotropy, and preferential alignment of BAp in each bone varies depending on the shape and stress conditions in vivo. In the mandible, complicated bone sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…This load‐dependent HA alignment has been reported by Nagisa et al. () that the biological apatite (BAp) forms in correlation with variations in stress distribution. In their study, the BAp in the bone formed differently depending on the force they bare.…”
Section: Discussionsupporting
confidence: 78%
“…This load‐dependent HA alignment has been reported by Nagisa et al. () that the biological apatite (BAp) forms in correlation with variations in stress distribution. In their study, the BAp in the bone formed differently depending on the force they bare.…”
Section: Discussionsupporting
confidence: 78%
“…Differences in the respective susceptibilities of BMD and BAp crystal orientation to local stress may explain this independence. 16,26) In comparison to BMD, BAp crystal orientation demonstrated more prominent localized effects of dentition.…”
Section: Resultsmentioning
confidence: 99%
“…Nakano et al demonstrated through experiments in monkey jawbones that the BAp crystallite basically aligns in the mesiodistal direction of the long axis, but reported that the crystallite aligns in the direction of occlusal pressure as a result of masticatory pressure in the vicinity of teeth 19) . Meanwhile, Nagisa et al examined BAp crystallite alignment in the alveolar and basal regions of rat jawbones, while Morioka et al and Furuya et al examined this in human jawbones, and reported the same results [20][21][22] . Following tooth extraction, the external form of the jawbone changes in response to multiple local and functional factors 25) .…”
Section: Discussionmentioning
confidence: 96%
“…It is a bone quality evaluation method that can be used to quantitatively evaluate BAp crystallite alignment in localized regions. Nakano et al used this method to examine the ulnae, calvaria and mandibles of experimental animals and suggested site speci city of BAp crystallite alignment 19,20) . Morioka et al and Furuya et al also used this method for detailed analysis of BAp crystallite alignment in human jawbone and reported that dentate mandibles exhibit a double structure on a nanoscale 21,22) .…”
Section: Introductionmentioning
confidence: 99%